Kościół w czasach Jana Pawła II, red. M. Rusecki, K. Kaucha, J. Mastej, Wydawnictwo KUL - Wydawnictwo Archidiecezji Lubelskiej "Gaudium", Lublin 2005, ss. 514 - Tomczak, Ryszard (Studia Nauk Teologicznych PAN, 2020)
Recenzja